Władze garnizonowe w Łodzi w latach 1945–1949 - Jarno, Witold (Acta Universitatis Lodziensis. Folia Historica, 2013)
The article describes the history of military garrison authorities in Łódź in the years 1945– 1945, and especially the process of creating, staffing, organization, and the main forms of activity. Garrison of Łódź in the first years after the Second World War was one of the biggest Polish Army garrisons. In Łódź stationed a lot of units and the military institutions. Additionally, from April 1945 to November 1946 in Łódź was located the command of the military district number six. In the years 1945–1949 commanders of the Łódź garrison were 6 officers: colonels Andrew Czartoryski, Mieczysław Melenas, Paul Ochremuszko, Marcel Domarecki and Joseph Batkiewicz and lieutenant colonel Joseph Bielecki. The activity of military garrison authorities was essential for the normal functioning of a large garrison. Creating a military garrison authorities in Łódź, accompanied by many difficulties, arising from the lack of qualified officers, war damage and supply problems. Commander of the garrison was responsible for the state of security and discipline in the garrison, guard duty, the allocation of training sites and firing ranges, the protection of military buildings, soldiers health and good cooperation with the civil authorities. Garrison in Łódź in the years following World War II well coped with most tasks, enabling military units and institutions in Łódź work in the best possible conditions at that time.